2014
DOI: 10.1021/la502964y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Proteins at the Solution/Air Interface Influenced by Added Nonionic Surfactants at Very Low Concentrations for Both Components. 2. Effect of Different Surfactants and Theoretical Model

Abstract: The influence of the addition of the nonionic surfactants dodecyl dimethyl phosphine oxide (C12DMPO), tetradecyl dimethyl phosphine oxide (C14DMPO), decyl alcohol (C10OH), and C10EO5 at concentrations between 10(-5) and 10(-1) mmol/L to solutions of β-casein (BCS) and β-lactoglobulin (BLG) at a fixed concentration of 10(-5) mmol/L on the surface tension is studied. It is shown that a significant decrease of the water/air surface tension occurs for all the surfactants studied at very low concentrations (10(-5)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Details of these calculations are discussed in [25]. Here we note that for BCS and a bubble radius of about 1.6 mm the optimum diffusion coefficient was several times larger than the physically realistic one, which is probably due to the presence of convection in the measuring cell.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Details of these calculations are discussed in [25]. Here we note that for BCS and a bubble radius of about 1.6 mm the optimum diffusion coefficient was several times larger than the physically realistic one, which is probably due to the presence of convection in the measuring cell.…”
Section: Resultsmentioning
confidence: 80%
“…To theoretically better describe the given experimental results we have to assume that at low concentrations the non-ionic surfactant increases the activity of the adsorbing proteins. A theoretical model which takes this effect into account will be discussed in later communication [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mixtures of non-ionic surfactants with more flexible proteins like β-casein (BCS) there is a sharp maximum in the dilational elasticity. Experimental results on the dilational rheology of protein/non-ionic surfactant mixtures were reported in 13-17 ; some of these results and the relevant theoretical models of the corresponding surface layers were discussed previously 18,19 . The influence of the addition of the non-ionic surfactants C 12 DMPO, C 14 DMPO, С 10 ОН and С 10 ЕО 5 at concentrations from 10 −5 to 10 −1 mmol/L to BCS and BLG solutions, respectively, at a fixed concentration of 10 −5 mmol/L on the surface tension were studied in 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a significant change ( The largest correction of this constant was found for the BCS+C 14 DMPO mixtures. 3 The solutions of proteins and surfactants studied here were the same as in 19 . The dilational rheology of individual solutions and their mixtures after equilibration of the system was studied using the buoyant bubble profile method at surface area oscillation frequencies in the range of 0.005 to 0.5 Hz.…”
Section: Introductionmentioning
confidence: 99%